Hepatic Hydrothorax: single centre’s experience in Malaysia on the utility of Octreotide - A case series - CK, vikneshwaran; skantha, ruben; Shahrani, Shahreedhan; Nik Muhamad Affendi, Nik Arsyad; jayaraman, thevaraajan; Chuah, Kee Huat; Stanley, khoo; Rajaram, Ruveena Bhavani; Mahadeva, Sanjiv (2023)
INTRODUCTION: Hepatic hydrothorax (HH) leads to significant morbidity and short-term mortality. Till date, transjugular intrahepatic portosystemic shunt (TIPS) and liver transplantation (LT) are the only definitive treatment for HH. OBJECTIVE: To determine the efficacy of octreotide infusion for management of HH. METHODOLOGY: Single-center retrospective case-series of decompensated liver cirrhosis patients with hepatic hydrothorax between March 2018 and March 2020. Apart from standard medical therapy, patients were subjected to pleural drainage and intravenous octreotide infusion over seven days (25mcg/hour day one, 50mcg/hour day two, 100 mcg/hour days three to seven). Resolution of HH was confirmed with repeat chest X-ray. RESULTS: Median age of patients in this case series was 69 years old [interquartile range (IQR) 62-74]; three males and five females. The median Child-Pugh Score was 8 (IQR 7-10) and model for end-stage liver disease (MELD-Na) score was 19 (IQR 14-22). All patients had concurrent ascites requiring peritoneal drainage. Seven had significant right-sided pleural effusion, whereas one had left-sided pleural effusion. Portal-vein thrombosis present in one patient and two had hepatocellular carcinoma. Four patients achieved clinical resolution of HH with octreotide at the end of treatment, and at one-, three-, six- and twelve-months post-treatment. Chemical pleurodesis done for one patient and another required repeat infusion of octreotide within one month with subsequent clinical resolution of HH. The remaining four patients did not achieve clinical remission; two patients required repeated thoracentesis during follow-ups, one patient had indwelling pleural catheter placement, and another transferred out to another hepatology center. CONCLUSION: Octreotide infusion in tandem with pleural drainage resulted in clinical resolution of HH in 50% of our patients and may be an alternative treatment for selected patients with HH when both TIPS and LT are non-viable.